A PHONO-STYLISTIC ANALYSIS OF ROSE MILLIGAN’S POEM DUST IF YOU MUST - Margaretta, Witness Eunike; Madi, Salwa Saleh; Rangkuti, Rahmadsyah (Journal of Language and Literature, 2023)
This research presented the stylistic analysis at the phonological level of Rose Milligan’s poem “Dust If You Must.” Through this poem, Rose Milligan beautifully emphasizes the importance of seizing our moment in life. Employing a qualitative data analysis approach, the study identified the five most prominent consonants and vowels, including /t/, /n/, /d/, /s/, /m/, and / ə/, /ʌ/, /ɪ/, /u/, /æ/, respectively. The data is displayed in four tables that show where these sounds appear in every line of the poem. The combination of these phonetic elements yielded words like ‘dust,’ ‘must,’ and ‘man,’ which strongly resonate with the poem’s theme. This focus on how the sounds in the poem connect to its meaning helps us understand the poem better. It shows that the poet chose these sounds on purpose to make the poem more meaningful. In addition, this emphasis on specific sounds can reinforce the themes and messages the poet intends to convey, deepening our comprehension of the connection between phonetics and interpreted meaning. This study has the potential to raise appreciation for literary works and support the development of new theories in stylistic analysis by providing a better understanding of how sounds in poems relate to the theme.